1992
DOI: 10.1007/bf02259124
|View full text |Cite
|
Sign up to set email alerts
|

Visual response properties of neurons in the middle and lateral suprasylvian cortices of the behaving cat

Abstract: The visual response properties of cells in the middle (MS) and lateral (LS) suprasylvian cortices were studied in alert cats, which were trained to fixate a spot of light and maintain fixation when a second test light was introduced in the midst of fixation. This second light served to test for visual sensitivity, and it could be moved at different speeds in any direction under computer control. Over half of the cells exhibited a visual response. With a small spot of light, most cells were directionally select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 59 publications
(71 reference statements)
2
12
1
Order By: Relevance
“…Using the vector-averaging technique of Yin and Greenwood (1992), we proved that the vast majority of corticotectal (81%) and corticostriatal (87%) neurons studied here were directionally selective, with similar values for the magnitude of directional bias (i.e., DSIs; see Yin and Greenwood, 1992). However, both the directional selectivity plots and the axial direction preference profiles of the two populations of neurons were very different.…”
Section: Directional Selectivitymentioning
confidence: 62%
See 2 more Smart Citations
“…Using the vector-averaging technique of Yin and Greenwood (1992), we proved that the vast majority of corticotectal (81%) and corticostriatal (87%) neurons studied here were directionally selective, with similar values for the magnitude of directional bias (i.e., DSIs; see Yin and Greenwood, 1992). However, both the directional selectivity plots and the axial direction preference profiles of the two populations of neurons were very different.…”
Section: Directional Selectivitymentioning
confidence: 62%
“…Quantif ying directional selectivit y. Directional selectivity in L S corticof ugal neurons was quantified using vector averaging from a method outlined previously (Goldberg and Brown, 1969;Yin and Greenwood, 1992). Data from a single direction of stimulus movement were considered a vector, the direction and magnitude of which corresponded to the direction of stimulus movement and the mean number of spikes evoked in eight stimulus presentations, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence in the literature demonstrating no effects of anesthetics on basic physiological properties and evidence indicating otherwise. Some studies in behaving animals that compared their results to those from anesthetized preparations using population data found no major differences (Wurtz, 1969;Yin and Greenwood, 1992). However, studies that compared single-unit activity before and after the administration of anesthetics (Goldstein, 1968;Walker and Teas, 1974;Young and Brownell, 1976;Brownell et al, 1979;Kuwada et al, 1989) invariably found significant effects of anesthetics in most, if not all, single units studied.…”
Section: Effect Of Anesthetics On Auditory-visual Bimodal Integrationmentioning
confidence: 99%
“…The area contains cells responsive to visual, auditory, and somatosensory stimuli (Symonds and Rosenquist, 1984a;Rosenquist, 1985;Olson and Lawler, 1987;Yin and Greenwood, 1992a), and has been implicated in the control of eye movements (Yin and Greenwood, 1992b).…”
Section: Appendixmentioning
confidence: 99%